NorthStar : - Beaumont, John (Pearson Longman, 2006)
NorthStar: Building Skills for the TOEFL® iBT: Intermediate, by John Beaumont (Series Editors: Frances Boyd and Carol Numrich) is published in cooperation with ETS. Pearson Longman and ETS combine their expertise in language learning and test development to create an innovative approach to building the skills assessed in the new TOEFL® Internet-based test (iBT). Each text features: Ten thematic units to develop academic skills in English while building test-taking confidence; Integrated skill practice to develop critical thinking and communicative competence; Authentic TOEFL® iBT practice sets created by ETS especially for this series; Practical tips to sharpen test-taking strategies; Teacher's Manuals with evaluation tools to track students' progress and actual student responses (speaking and writing) at all score levels.